The State of Earnings Management in India : An Empirical Analysis - Kaur, Raghuveer; Mehra, Sanachit; Khanna, Ashu (Indian Journal of Finance, 2015)
Earnings management has become an area of concern after the fall of giant enterprises. The fall of Xerox, Worldcom, Satyam, and Enron posed a threat to investors’ confidence. Undoubtedly, countries like India, which are quickly developing, have to be more precise with their corporate governance practices. The Securities and Exchange Board of India (SEBI) mentioned that in India, the average earnings management is 2.9%. In an attempt to estimate the level of earnings management, the study analyzed the earnings management levels across various sectors of the economy. The study attempted to understand the state of earnings management in India for a period of four years (2010-2013) across seven sectors of India. These seven sectors included : (a) hotels, (b) forging, (c) chemical and fertilizers, (d) healthcare, (e) fast moving consumer goods (FMCGs), (f) non-electrical, (g) consumer durables. The study considered a total of 1027 companies for analysis. The study also checked the predictability of the modified Jones model in detecting earnings management for each sector under consideration in this study.